Bifunctional Nanocomposites Formed from Magnetic Lignin-Derived Carbon and Molybdenum Disulfide for Efficient Pollutant Removal - Sanchez-Poblete, J (Elsevier B.V., 2024)
The development of inexpensive and robust bifunctional nanocomposites toward efficient pollutant removal is crucial for wastewater remediation. Herein, we report a novel strategy for fabrication of magnetic nanocomposites loaded with molybdenum disulfide (Fe3O4/PLC-MoS2) using lignin biomacromolecules for efficient pollutant removal. The Fe3O4/PLC-MoS2 exhibit excellent pollutant removal capacity: The adsorption capacity of Pb(II) achieve 236.1 mg/g and the methylene blue (MB) degradation rate is up to 90.0 % within 20 min. The adsorption mechanism reveal that the enhanced removal properties is due to that the S atoms on the loaded MoS2 could convert into soluble sulfide and react with Pb(II) to form white precipitate β-Pb3O2SO4. Moreover, the experiments results demonstrate that the Fe3O4/PLC-MoS2 has a low bandgap, which can activate PMS to produce reactive oxygen species and degrade MB molecules efficiently. Notably, the Fe3O4/PLC-MoS2 demonstrate continued outstanding wastewater remediation capabilities even in scenarios where Pb(II) and MB coexisted. Overall, this study offers a viable and eco-friendly design of dual function removal material by using lignin waste toward promising implications for wastewater treatment. © 2024 Elsevier B.V.